Prevalence and antifungal susceptibility of gastrointestinal candidiasis among diabetic patients: A cross-sectional study - Anthony P. Oyom; Emmanuel Okello; Victoria Acam; Christine Aramo; Bashir Mwambi; John C. Okiria; Caesar Oyet (AOSIS, 2020)
Background: Gastrointestinal candidiasis is the most predominant opportunistic human mycosis, especially in diabetic patients. There is a global increase in antifungal resistance coupled with a rarity of information on antifungal susceptibility profiles in Uganda. Objective: This study aimed to determine the occurrence and antifungal susceptibility of gastrointestinal candidiasis in diabetic patients. Methods: Stool and fasting blood specimens were obtained from randomly sampled consenting patients with diabetes mellitus at St. Francis Hospital Nsambya in Kampala, Uganda to determine Candida infection, fasting blood glucose and glycated haemoglobin levels. Susceptibility testing was performed on Muller Hilton agar supplemented with 2% glucose and 0.2 µg of methylene blue, using the E-test diffusion method. Results: Among the 241 patients included in the analyses, the overall prevalence of gastrointestinal candidiasis was 15.4% (n = 37). Candida albicans (62.16%, n = 23) was the predominant species, followed by Candida glabrata (18.92%, n = 7), Candida tropicalis (8.11%, n = 3), Candida krusei (5.41%, n = 2) and Candida dublinensis (5.41%, n = 2). Resistance was observed with miconazole (48.65%), clotrimazole (18.92%) and fluconazole (8.11%). No resistance to itraconazole and nystatin was observed. Gastrointestinal candidiasis was associated with poor glucose control (p ≤ 0.001), prior use of antibiotics (p ≤ 0.001), antifungals (p ≤ 0.001) and corticosteroids (p ≤ 0.001) and was more common among female patients (p = 0.01). Conclusion: Occurrence of gastrointestinal candidiasis was relatively low among our participants, and infection was associated with poor glucose control, female sex and use of antifungals, antibiotics and corticosteroids.